A simulation study on risk emergence mechanism and transmission path of coal mine workers’ unsafe behaviours based on DEMATEL-ISM and Arena simulation - Lujie Zhou; Menghan Wang; Kai Yu; Tianyu Wang; Zhaoxiang Mu; Zhenyue Wang (Scientific Reports)
Abstract In coal mine production activities, unsafe behaviours of workers are one of the important factors leading to frequent accidents, with the complexity of risk transmission mechanisms posing significant challenges to safety management. To systematically reveal the risk transmission rule of unsafe behavior risks, this study proposes a multidimensional research methodology: First, based on 574 coal mine accident investigation reports from 2019 to 2024, text mining techniques were employed to extract 26 key influencing factors, establishing an indicator system encompassing five dimensions: environment, individual, group, organizational management, and leadership. Second, an integrated DEMATEL-ISM method was adopted to construct a hierarchical structure model of influencing factors, identifying work experience and psychological status as fundamental causal nodes. And then, Arena simulations revealed risk transmission rule: When the mean risk emergence rate increased from 0.5 to 2, the system’s residual risk entropy nearly diminished to zero. Enhanced node immunity (up to node 5) significantly reduced both system risk entropy and residual risk entropy. However, continued improvement of node 11’s immunity showed diminishing marginal effects, indicating that appropriately enhancing node 11’s immunity effectively reduces accident probabilities. Finally, targeted control strategies were proposed across five dimensions: safety management, individual factors, group dynamics, safety leadership, and physical environment. The results of this study can provide important theoretical support and practical guidance for coal mine safety production, help to reduce the accident rate, ensure the life safety of coal mine workers and the sustainable development of enterprises.